Perempuan Hamil Di Balik Jeruji: Evaluasi Efektivitas Program Perlindungan Dalam Lapas - Djian Fadilla; Mitro Subroto (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2023)
This article aims to review and evaluate the effectiveness of protection programs implemented in prisons for pregnant women in detention. In this context, we analyze aspects of physical and mental health, legal and reproductive rights, and alternatives available to pregnant women in prison. The evaluation is based on empirical data obtained through field studies, interviews with prison officials, and a review of existing policies. The results reveal the challenges faced by pregnant women in the prison system and provide a basis for improving more effective and human rights-oriented protection programs.